2001
DOI: 10.1016/s0002-9440(10)62513-8
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Fibers Express Major Histocompatibility Complex Class II Antigens Independently of Inflammatory Infiltrates in Inflammatory Myopathies

Abstract: The aim of our study was to address the question of whether muscle fibers express major histocompatibility complex (MHC) class II in inflammatory myopathies. For this purpose we performed a systematic study of MHC class II antigen expression on muscle fiber membranes in muscle tissue from polymyositis and dermatomyositis patients in various stages of disease activity. Thirty-two patients with classical clinical signs of myositis were divided into subgroups depending on duration of clinical signs of myositis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 33 publications
3
96
1
8
Order By: Relevance
“…The independence of MHC expression in muscle fibres from the presence of adjacent inflammatory cell infiltrates has also been noted in previous studies [15,[44][45][46][47]. This was observed in both the early and late chronic phases of the disease, and in symptomatic and asymptomatic muscles from the same individuals [48,49]. However, in the present study we found that, unlike MHC-I, there was a significant association between MHC-II expression and the presence of inflammatory infiltrates in the IIM group.…”
Section: Text 14supporting
confidence: 81%
“…The independence of MHC expression in muscle fibres from the presence of adjacent inflammatory cell infiltrates has also been noted in previous studies [15,[44][45][46][47]. This was observed in both the early and late chronic phases of the disease, and in symptomatic and asymptomatic muscles from the same individuals [48,49]. However, in the present study we found that, unlike MHC-I, there was a significant association between MHC-II expression and the presence of inflammatory infiltrates in the IIM group.…”
Section: Text 14supporting
confidence: 81%
“…Additionally, IFN-␄ and TNF may induce up-regulation of MHC class I or II Ags in muscle fibers which is a characteristic finding in patients with polymyositis or dermatomyositis but not in differentiated fibers from healthy individuals (43). Expression of MHC molecules on muscle fibers could allow T cell-muscle cell interaction, but this has been regarded unlikely because the costimulatory molecules CD80/86, normally required for functional interaction, are not expressed by inflamed muscle fibers (44,45). Still, T cells independent of costimulation by CD80/86, such as CD28 null T cells, could be activated following interaction with MHC-expressing muscle fibers and cause muscle fiber damage.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the diagnosis of PM or DM was confirmed by typical histopathologic changes including inflammatory infiltrates in another biopsy specimen, by changes on electromyograms, or by the typical skin rash in DM (Table 1). Clinical data on some of these 14 patients have been presented previously (27). The median age at the time of biopsy was 46 years (range 26-61 years).…”
Section: Methodsmentioning
confidence: 99%